Potencial ovicida de Pochonia Chlamydosporia Pc-10 (Ascomycota: Sordariomycetes) sobre massas ovígeras de Pseudosuccinea columella (Mollusca: Gastropoda) e ovos de Fasciola hepatica (Trematoda: Fasciolidae) como alternativa de controle biológico - Castro, Lorena Souza (2018)
Molluscs belonging to the species Pseudosuccinea columella show aquatic behavior and inhabit sweet water collections located especially in neotropical regions. They are hermaphrodite snails, having high reproductive capacity and with ovigerous masses placed in substrates submerged in the borders of the breeding places exposed to the dryness and pathogens like fungi. Trematodes of the genus Fasciola are parasites of the bile ducts and cause great economic losses. Snails, are the first intermediate hosts of the specimen Fasciola hepatica and its control is one of the tools for the control of fasciolose. Virtually nothing is known about the susceptibility of ovigerous masses to fungi. For the first time, the susceptibility of P. columella ovigerous masses to the fungus Pochonia chlamydosporia (Pc-10 isolate) was demonstrated under laboratory conditions. For this, two experimental groups were constructed: the control group, in which it did not verify the exposure to the fungus, and the treated group, characterized by the exposure of the ovigerous masses to the fungal isolate (Pc-10) during 25 days. The entire experiment was conducted in duplicate consisting of five replicates for each replicate, using a total of forty ovigerous masses. Weekly, throughout the experiment, the ovigerous masses of both experimental groups (control and treated) were analyzed under the aid of a stereoscopic microscope for the accounting of hatched molluscs. In parallel to this study, the ovicidal potential of the P. chlamydosporia fungal extract of the strain (Pc10) in 900 eggs of F. hepatica was evaluated. For this, the eggs were previously embryonated in B.O.D and later to stimulate the miracidial hatching, were exposed to artificial light and controlled temperature, from which it was inoculated in the medium containing the eggs and the fungus extract in different concentrations. The results revealed that the embryogenesis process was inhibited by the ascomycete in question, suggesting its applicability in biological control programs of this limneid. In 10 addition, the ultrastructure revealed the occurrence of different types of interactions established between the ovigerous masses of the mollusc with the mycelia of P. chlamydosporia, which resulted in important structural modifications in these, compromising, therefore, the viability of the eggs. In relation to the enzymatic fungal extract, both interfered significantly in the viability of the eggs, the mycelium being dependent on days for growth and establishment of the fungus in ovigerous masses and the extract being efficient evaluated in a period of 60 minutes, on concentrations in which the smaller dosages, there was egg collabiation and in larger, partial disintegration of the external structure and rupture